Characteristics of the new coronavirus infection (COVID-19) in patients with systemic sclerosis - M. N. Starovoytova; O. V. Desinova; L. P. Ananieva; O. A. Koneva; L. А. Garzanova; O. B. Ovsyannikova; R. U. Shayakhmetova (Современная ревматология)
Interest to the topic of coronavirus infection remains unabated. At the same time, there is insufficient information in the literature on the clinical course of COVID-19 in systemic sclerosis (SSc), a systemic autoimmune disease associated with high mortality.Objective: to identify the characteristics of coronavirus disease in SSc and risk factors for severe COVID-19 and death.Material and methods. A retrospective analysis of data from patients with SSc was performed. The analyzed cohort included patients from the registry of the Systemic Sclerosis Laboratory of V.A. Nasonova Research Institute of Rheumatology. Information about the history of novel coronavirus infection was obtained by telephone interview 10 months after the outbreak of the pandemic. COVID-19 was diagnosed if there was a positive oral cavity/nasopharynx PCR swab, if antibodies to SARS-CoV-2 were present and/or characteristic symptoms and computed tomography (CT) changes in the lungs were present.Results and discussion. COVID-19 was diagnosed in 57 (52%) patients with SSc. Their median age was 58 [31; 79] years. The majority were women (n=48, 84%) with a limited form of SSc (n=37, 65%). Fifteen (26%) patients had diffuse, 4 (7%) had overlapping (SSc-polymyositis and SSc-rheumatoid arthritis) and 1 (2%) had visceral SSc. Almost 2/3 (74%) of patients with COVID-19 had SSc associated with interstitial lung disease (ILD), with 40% of them having >20% lung parenchymal involvement.All patients received low-dose prednisone therapy, 95% received immunosuppressive therapy and in half of the cases mycophenolate mofetil; rituximab was used in 40% of patients.Chest CT scan was performed in 51 (89%) patients. Pneumonia caused by the new coronavirus infection was detected in 46 (90%) of them: CT1 (up to 25% lung involvement) – in 10 (20%), CT2 (25–50% involvement) – in 21 (41%) and CT3 (50–75% involvement) – in 15 (29%); in 5 (10%) cases no changes were detected on CT.Mild and moderate course of the viral infection was observed in 19 (33%) and 18 (32%) patients respectively, severe infection – in 20 (35%), including fatal cases in 12 (21%).Conclusion. Patients with SSc infected with SARS-CoV-2 are at risk of severe coronavirus infection, often due to the association of the underlying disease with ILD and the use of immunosuppressive therapy, including biologic disease-modifying antirheumatic drugs. In case of COVID-19 development the high incidence of cardiovascular and pulmonary comorbidities that characterize SSc may contribute to a decrease in the efficacy of therapy for both the underlying disease and coronavirus infection, generally worsening the prognosis in these patients.